2014
DOI: 10.1590/0102-311x00085313
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with gestational weight gain in pregnant women in Rio de Janeiro, Brazil, 2008

Abstract: Inadequate weight gain during pregnancy is an important predictor of complications for the mother and infant. This cross-sectional study assessed factors associated with inadequate weight gain among women in the third trimester of pregnancy who received prenatal care under the Brazilian Unified National Health System (SUS) in the city of Rio de Janeiro, Brazil, from November 2007 to July 2008. A total of 1,079 pregnant women were interviewed, and adequacy of weight gain was obtained by calculating weight gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
4
16
0
6
Order By: Relevance
“…This data suggests that women who enter pregnancy when overweight have reduced chances of getting inadequate gestational weight gain as compared to those with normal BMI or underweight. Our findings are in agreement with the findings of other studies done in Brazil and England [24, 25]. It is also important to note that the mean rates of GWG for underweight and normal weight participants during second and third trimester were lower and significantly different from those recommended by the Uganda MoH.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This data suggests that women who enter pregnancy when overweight have reduced chances of getting inadequate gestational weight gain as compared to those with normal BMI or underweight. Our findings are in agreement with the findings of other studies done in Brazil and England [24, 25]. It is also important to note that the mean rates of GWG for underweight and normal weight participants during second and third trimester were lower and significantly different from those recommended by the Uganda MoH.…”
Section: Discussionsupporting
confidence: 92%
“…This is close to 32.5% that was found by Farhana et al , (2015) in their study on Malaysian pregnant women in the rural area [11]. However, our finding of is lower than the 27.5% and the 27.7% that were reported in urban Brazil and urban Malaysia respectively [24, 25]. Although our prevalence of women gaining adequate gestational weight is low, it is higher than the 3.1% that was reported in Nigeria [10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…High percentages of inadequate GWG were reported from low-income Sub-Saharan African countries (80% and 71.8% from Malawi [28,56], 69.3% and 67.2% from Ethiopia [2,35], 63% from Niger [58], 62.7% from Uganda [9], and 58.8% from Democratic Republic of Congo [59]) compared to middleincome countries (28% and 36.9% from Cameroon [45,47], 15.7% and 24% from South Africa [54,55]). Unlike in other high-income [20,24,62,63] and middle-income [64] countries where many pregnant women experience excessive GWG, all of the studies from low-income Sub-Saharan countries [2,9,28,35,56,58,59] reported that more than 58% of pregnant women experienced inadequate GWG. This could be due to the inability of women to consume adequate food because of accessibility and affordability problems [65].…”
Section: Discussionmentioning
confidence: 98%
“…Studies from Belgium, Canada and Sweden demonstrated an inverse association (but the association only being apparent in those with healthy pre-pregnancy weight in the Swedish study) [49][50][51], while nine studies from Iran, USA, Australia/New Zealand, Brazil and the Netherlands found no association [52][53][54][55][56][57][58][59][60]. One study from New York found that the relationship was complex and depended upon area of residence [61].…”
Section: High Maternal Weight Gain In Pregnancymentioning
confidence: 99%